PERAN KEADILAN PROSEDURAL DALAM MEMBANGUN PERILAKU KEWARNEGARAAN ORGANISASI DIMEDIASI KEPERCAYAAN PADA PIMPINAN DAN KETERLIBATAN KERJA - Pahlawi, Lukman Ahmad Imron; Cahyono, Agus; Utomo, Agus (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to examine the role of procedural justice in building organizational citizenship behavior (PKO) by mediating trust in leaders and work involvement in the Tawangharjo District Office, Grobogan Regency. The study uses a quantitative approach with a sample of 83 village devices selected using the census method (total sampling). The data were analyzed using validity, reliability, linearity, path analysis, and mediation analysis with the Hayes bootstrap process. The results of the study show that procedural fairness has a significant effect on trust in leadership and work involvement. In addition, procedural fairness, trust in leadership, and work involvement each have a significant influence on PKO. Specifically, trust in leadership and work involvement mediate the relationship between procedural justice and PKO significantly. Simultaneously, procedural fairness, trust in leadership, and work involvement contributed significantly to PKO. These findings also show that the direct influence of procedural justice on PKO is more dominant and significant than other factors.